Preparing Students for Mathematics Lessons and Checking Their Knowledge of Mathematics - Sunnatullo DO’STOV; Xushboqova Saodat Qo’chqor qizi; Jumayeva Mashxura Yoqubjon qizi; Abdijalilova Mohiniso Axmad qizi (Global Scientific Publishing, 2022)
This article describes in detail the preparation of students for mathematics lessons and the examination of their knowledge of mathematics, the analytical and logical thinking ability of a student who has mastered mathematics well, and the examination of students' level of mastery in various ways
Keywords: mathematics lesson; lesson structure; lesson preparation; work plan